Remote Sensing in Atmospheric Studies: Enhancing Understanding of Climate Dynamics and Air Quality, Atmospheric Monitoring and Analysis; Emerging Technologies and Future Directions - Arya (International Journal of Atmosphere, 2025)
Remote sensing has emerged as a transformative tool in atmospheric sciences, providing detailed and comprehensive insights into various atmospheric phenomena. Its advanced capabilities have revolutionized our understanding of climate dynamics, air quality, and atmospheric composition, enabling more accurate monitoring and analysis. This paper reviews the critical role of remote sensing technologies in enhancing knowledge of atmospheric processes and their practical applications in areas such as climate change monitoring, air pollution tracking, and weather forecasting. Recent advancements in satellite-based observations, ground-based measurement systems, and innovative remote sensing instruments have significantly improved the precision and scope of atmospheric studies. Emerging technologies, such as hyperspectral imaging and lidar, further demonstrate the potential of remote sensing to address complex environmental challenges.Additionally, the integration of satellite data with ground-based observations and sophisticated data analytics offers a robust approach to addressing pressing global concerns, including the mitigation of climate change impacts and the improvement of air quality. The synergy between traditional meteorological methods and cutting-edge remote sensing systems facilitates better prediction models, enhances real-time data acquisition, and contributes to proactive environmental management strategies.This paper places special emphasis on the evolving landscape of remote sensing applications and the interdisciplinary efforts required to maximize its potential. The discussion extends to the challenges faced in deploying these technologies globally, particularly in resource-constrained regions, and the importance of international collaboration to overcome such barriers. By outlining key research priorities and future directions, this review aims to provide a roadmap for leveraging remote sensing advancements to address the multifaceted challenges in atmospheric sciences, ultimately contributing to a more sustainable and resilient future.
Keywords: Air quality; atmospheric studies; climate dynamics; data analytics; emerging technologies; future directions; remote sensing; satellite observations